The importance of civil society in supporting local communities to achieve sustainable development - Meziani, Brahim (The International tax journal, 2026)
This article provides a comprehensive study on the role of civil society in supporting local communities to achieve sustainable development, by focusing on the interactive relationship between civil society and local authorities, as well as the mechanisms of public participation in decision-making and development. The study begins by defining the basic concepts of civil society and local communities, while reviewing the evolution and emergence of civil society through Western and global political thought. It also highlights its characteristics and diverse functions, which include social, economic, and political dimensions, in addition to its role in promoting accountability, transparency, and combating corruption. The article further discusses local communities in Algeria, including their types, functions, and resources, while emphasizing the importance of partnership between these communities and civil society organizations in planning, implementation, and monitoring of development projects, in order to ensure that development responds to the real needs of citizens. The research also highlights the importance of establishing a legal and regulatory framework that supports the independence of civil society and enhances its effectiveness, as well as the need to activate platforms for community dialogue, encourage volunteer work, and promote a culture of transparency and accountability.